If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(z + -913) = 315 Reorder the terms: 9(-913 + z) = 315 (-913 * 9 + z * 9) = 315 (-8217 + 9z) = 315 Solving -8217 + 9z = 315 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '8217' to each side of the equation. -8217 + 8217 + 9z = 315 + 8217 Combine like terms: -8217 + 8217 = 0 0 + 9z = 315 + 8217 9z = 315 + 8217 Combine like terms: 315 + 8217 = 8532 9z = 8532 Divide each side by '9'. z = 948 Simplifying z = 948
| 21-5h=h+6 | | 13(-6x)+15=375 | | 14(t-910)=476 | | -5p+3=43 | | .80x+.20(70)=.70(70+x) | | .80x+.25(70)=.70(70+x) | | 4(s-859)=344 | | (x-2)=12(y-3) | | 2x+76=170 | | X+2y-7=6 | | (R/3)-4=11 | | x+2+x+4+x=180 | | 5x/3-2=13 | | 4(2-3b)=6b-4(b+5) | | 4(3x-2)-3=4(x-3)+33 | | 8m+20=2m | | 8(z-927)=256 | | 24a=6a*4 | | 300=x+75 | | 2y-7/y | | Y-7=14.1 | | 240=x-60 | | 25-6[(2-7)-(-5-7)]= | | 6(2x-5)=5(3x+7) | | 7(4x+1)=5(4x+3) | | 3(5-4x)=3(3x+4) | | 5(X+3)+(2X-7)=3X-9 | | 1/3,47/6 | | 82-k=37 | | x^2-3x+62=0 | | 240=x+75 | | 5x-7=2x-67 |